Interactive Storytelling in the Library - Ramirez, Melanie A. (Chophayom Journal, 2016)
This paper aimed to investigate the effectiveness of using interactive storytelling technique in the library. Interactive Storytelling is to give both beginning and experienced storytellerses- pecially those who work in a library and also adults who work with children in Head Start programs, day care centers, museums and other recreational places where children gathera sense of the role of storytelling in human history; an understanding of the importance of story in a child’s life; basic information about how to choose, prepare and tell stories; program planning guidance; and ways to gain administrative and community support for interactive storytelling as an important part of library service to children. Professional li-brarians knows the SKILLS ON STORYTELLING (Interactive): What makes a Story Tellable?; What kinds of stories are needed in a storyteller’s Repertoire?; Basic steps in Learn-ing a Story; Telling the Story; and Qualities of a GOOD Storyteller. Librarians can be story-teller that can encourage parents to read and tell stories to their young children every day with interactive; they can teach older children and teenagers how to tell stories interactive in the library; and they can also conduct storytelling workshops for day-care staff and other adults who work with children. Interactive Storytelling is an excellent means of introducing children to the wonderful world of books while building positive attitudes for reading. The exposure to oral language patterns helps developing children’s listening sub-skills. This study has also conducted techniques on interactive storytelling to children in the library setting.